Effects of coffee consumption on cholesterol, glucose, lactate and triglyceride levels during exercise in the heat among female university students - Zaki, Noor Imani Mohd (2021)
Introduction : Coffee is a complex mixture of chemicals and is the main source of caffeine. People have been drinking coffee for the last thousand years and throughout its history, many theories have been reported on its possible health benefits, including regulating metabolism and thermoregulation. Objective : To investigate the effect of coffee consumption on thermoregulation and selected metabolic blood profile during exercise in the heat among female university students. Methods : Seventeen moderately active female university students aged between 19 to 40 years old were randomly assigned to start with either caffeinated coffee or decaffeinated coffee trials. Participants were given a standardised breakfast (two slices of white bread, 300 ml of caffeinated coffee or decaffeinated coffee and 300 ml of plain water) to be consumed 30 mins prior to the walking exercise. Participants’ body weight was measured before and after exercise to calculate percentage of body weight loss. Blood samples were also collected before the coffee was drunk, 10-mins after coffee was drunk, post 30-min walking exercise and post 10-min recovery time. Pre- and post-exercise urine were also checked for osmolality using the Urine Specific Gravity (USG). Pre-exercise urine was checked before they took their breakfast, and post-exercise urine was checked after they finished the experiment. The participants walked on the treadmill for 30 min at a speed that would elicit the participant’s heart rate reserve (HRR) in the moderate intensity of 60% with environmental conditions of 300C and 70% relative humidity. Heart rate and tympanic temperature were recorded at 5 minutes intervals. The rate of perceived exertion (RPE) was recorded at 10 min intervals. During 10 min recovery, heart rate, and core body temperature were recorded at 5 min intervals. Finger-pricked blood was collected at four time-points: pre-exercise after 8 hours of overnight fasting, at post-10 min coffee drinking, immediately after the exercise trial completion, and post 10 min after exercise completion. Blood samples were analysed for cholesterol, glucose, lactate, and triglyceride levels. Results : There were no significant effect of caffeinated coffee on the heart rate, hydration status, body core temperature, rate of perceived exertion (RPE), blood cholesterol levels, and blood glucose levels during exercise trials in the heat among female university students ( p > 0.05). There were significant effects of caffeinated coffee on blood lactate (p = 0.014) and blood triglyceride levels (p = 0.002) during exercise between trials in the heat among female university students. Blood lactate and blood triglyceride levels increased during exercise in the heat with caffeine ingestion. Conclusion : There were no significant effects of caffeinated coffee on heart rate, hydration status, body core temperature rate of perceived exertion (RPE), blood cholesterol and blood glucose levels. However, consumption of caffeinated coffee 30 min prior to exercise had a significant effect on blood lactate and blood triglyceride levels. Blood lactate and blood triglyceride levels increased during exercise in the heat with caffeine ingestion.